Cobalt ferrite/cellulose membrane inserted catalytic syringe filter for facile in-situ filtration/degradation of emerging organic pollutants in water via activating peroxymonosulfate. (August 2022) - Wu, Ying; Xu, Lijie; Shi, Jiangtao; Cui, Juqing; Han, Shuguang; Xia, Changlei; Gan, Lu
Graphical abstract: Highlights: CoFe2 O4 /cellulose membrane was prepared and used as catalytic syringe filter. The filter could in-situ degraded organic pollutants via syringe-driven filtration process. Radical and high-valent metal-oxo species were responsible for pollutant degradation. The filter showed promising stability and adapability. Negligible cobalt ions were leached. Abstract: In this study, a novel membrane was prepared from CoFe2 O4 deposited commercial cellulose filter paper, and employed in the design of a catalytic syringe filter. The filter was used for the removal of various synthetic organic chemicals (SOCs) including rhodamine B, dimethyl phthalate, bisphenol A, ibuprofen, norfloxacin, 4-chlorophenol and diclofenac in water through in-situ activating peroxymonosulfate, which simulated an actual syringe-driven filtration process. The impact of SOC concentration, injection speed, series-connected filter number on the in-situ filtration/degradation performance of the filter were systematically investigated. The results demonstrated that the prepared filter had excellent catalytic capability towards all mentioned SOCs. Specifically, three series-connected filters could completely degraded SOCs even when the concentration of each SOC was higher than 0.1 mM. ESR and quenching tests indicated that the OH and SO4 − were main radical species dominating the SOC degradations. Meanwhile, high-valent metal-oxo species were also generated which participated in the SOC degradations. Furthermore, the filter had promising longtime use stability which maintained its effectiveness for 2 h of uninterrupted water flow. This study provides a facile and practical means to introduce advanced oxidation techniques for organic pollutant removals in actual wastewater through syringe-driven in-situ membrane filtration/degradation process.